Precise Structure of Acidic Polysaccharide Present in Salvia Hydrogels - Rike Yudianti; Myrtha Karina; Masahiro Sakamoto; Jun-ichi Azuma (Masyarakat Peneliti Kayu Indonesia, 2010)
Precise structures of acidic ß-(1,4)-xylan in the hydrogels from three species of Salvia (S. miltiorrhiza (SM), S. sclarea (SS) and S. viridis (SV)) were characterized. SS and SV contained two different acidic residues (4-O-methylglucuronic acid (MeGlcA) and glucuronic acid (GlcA)) substituted at O-2 of ß-(1,4)-linked xylopyranose residues, whereas MeGlcA is absent in SM. Molar ratios of xylose to uronic acid are 2.0 : 1.0 (SM), 1.7 : 1.0 (SS), 1.4 : 1.0 (SV). Distribution of acidic residues in the ß-(1,4)-xylan chains was analyzed by Matrix-Assisted Laser Desorption/Ionization (MALDI)/Time of Flight (TOF) mass spectroscopy after reduction and partial hydrolysis. The results showed that many series of ions appeared as sodium adducts [M+Na]+, indicating that uronic acid residues are randomly and mixed distributed in xylo-oligosaccharide chains in the SS and SV xylans. All species showed presence of oligosaccharides in ranges of m/z 833.3 2561.2 (SM), 657.2 1655.5 (SS) and 731.2 1421.5 (SV). Acidic residues in SS and SV are distributed in shorter xylo-oligosaccharides than those in SM, although complicated substituted profiles with MeGlcA and GlcA were similarly detected in SS and SV. Presence of long free xylan chains in the SM oligosaccharides supported lower number of substituent in its xylan backbone.